2023
DOI: 10.1088/2057-1976/acde82
|View full text |Cite
|
Sign up to set email alerts
|

EEG motor imagery classification using deep learning approaches in naïve BCI users

Abstract: Motor Imagery (MI)-Brain Computer-Interfaces (BCI) illiteracy defines that not all subjects can achieve a good performance in MI-BCI systems due to different factors related to the fatigue, substance consumption, concentration, and experience in the use. To reduce the effects of lack of experience in the use of BCI systems (naïve users), this paper presents the implementation of three Deep Learning (DL) methods with the hypothesis that the performance of BCI systems could be improved compared with baseline met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…This section presents the CSP configurations used in this study: CSP, FBCSP, and Filter Bank Common Spectral Spatial Patterns (FBCSSP). For more information on each of the methods, please refer to our previous works [26,32]. A graphical representation of each of the CSP variations is shown in Figure 1.…”
Section: Csp-based Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This section presents the CSP configurations used in this study: CSP, FBCSP, and Filter Bank Common Spectral Spatial Patterns (FBCSSP). For more information on each of the methods, please refer to our previous works [26,32]. A graphical representation of each of the CSP variations is shown in Figure 1.…”
Section: Csp-based Methodsmentioning
confidence: 99%
“…Several authors have reported the use of a mutual information-based feature selection stage, which was implemented in this study to obtain more selective features from EEG signals [19]. In addition, previous works have demonstrated that filter banks of 8-15 Hz, 15 -22 Hz, and 22-30 Hz show adequate accuracy rates for binary classification [26,32]. Note that this method uses spectral filtering (using the filter bank) and spatial filtering through the CSP layer, which is implemented following the same configuration presented in the previous section.…”
Section: Selective Frequency Cspmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [27] proposed a hybrid 2D CNN-LSTM model for MI EEG classification. Guerrero-Méndez et al [28] applied various models, such as the Convolutional Neural Network (CNN), Long Short-Term Memory (LSTM)/Bidirectional Long Short-Term Memory (BiLSTM), and a combination of CNN and LSTM, in the same context (MI EEG).…”
Section: Introductionmentioning
confidence: 99%